Optimalisasi Bank Sampah Berbasis Pemberdayaan Perempuan di Desa Gunung Sari - Qomariah Imelda, Dewi; Budiarti, Ika Niswatin; Soimah, Nurus; Lail, Jamilatul; Wulandari, Tutik; Nabil, Muhammad (Keris: Journal of Community Engagement, 2023)
Gunung Sari Village is one of the villages that is developing a tourist village. Environmental cleanliness is certainly one of the priority problems that must be resolved by the village government. At the end of 2022, the Mandiri Women's Waste Bank KSM, Gunung Sari Village, was formed, consisting of mothers receiving the Family Hope Program (PKH), currently numbering 27 people. However, until now the Mandiri Women's Waste Bank KSM has not been running optimally because only a small portion of the community are members. Carrying out this activity is not only to maintain the cleanliness of the village environment but can also provide economic benefits for the community. The implementation of this service supports government programs related to the green economy where the implementation of this activity aims to empower and improve community welfare through the use of plastic waste/waste. The problems experienced by partners are related to the production and management fields, namely regarding the availability of waste bank tools, organizational management, business management and membership issues. This activity will focus on efforts to optimize village waste banks by 1) providing waste bank infrastructure, 2) organizational and business management training, 3) large-scale outreach regarding village waste banks